Reinvestigating atomic ordering in K 0.5 Na 0.5 NbO 3 and its impact on ferroelectric properties - Tripathi A.; Tripathi S. (My University, 2025)
In the present work, we reinvestigate the atomic ordering of a Pb-free morphotropic phase boundary (MPB) composition v i z . , K 0.5 Na 0.5 NbO 3 (KNN50) and its vicinity at various length scales using high-resolution x-ray diffraction and pair distribution function data. We have observed a monoclinic phase (Space Group: Pm) at long/short ranges differing from a very recent report by Saha et al 2024 J. Phys.: Condens. Matter 36 425703. Moreover, the ferroelectric (polarization) dominance of short-range ordering (SRO) over long-range ordering (LRO) has been observed and quantified for the very first time using the amplitude of the ferroelectric frozen phonon mode ( Γ 4 − ) (corresponding to the high symmetry cubic phase), thereby structure is linked with ferroelectric (or polarization) property for a widely studied MPB system v i z . , K x Na ( 1 − x ) NbO 3 (KNNx for x = 0.40, 0.50, and 0.60). Two uniquely identified monoclinic phases has been observed for SRO ( M SRO ) and LRO ( M LRO ) for all the compositions. The amplitude of ferroelectric frozen phonon mode ( Γ 4 − ) corresponding to M SRO is significantly higher ( ≈ 150 % − 180 % ) than M LRO . A peak is observed in the amplitude of Γ 4 − and intensity of prominent Raman peaks (ν1 and ν5) for x = 0.50, which is held responsible for high physical properties v i z . , dielectric permittivity, piezoelectric coefficient, remnant polarization, electromechanical coupling coefficient, and many more widely reported in literature for KNN50. © 2025 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.